Mechanical and thermal properties of compatibilized waste office white paper-filled low-density polyethylene composites - A., Faisal; Salmah, Husseinsyah, Dr. Ir. (SAGE Publications, 2013)
Link to publisher's homepage at http://www.uk.sagepub.com/